Pseudognaphalium munoziae (Gnaphalieae, Asteraceae): A new South American species from Chile - Freire, Susana E.; Monti, Claudia; Moreira-Muñoz, Andrés; Bayón, Néstor D. (Phytotaxa, 2013)
Pseudognaphalium is a large genus with about 90 species distributed worldwide, but with most species in America, and some in Asia, and Africa. A new species, P. munoziae, from the north of Chile (Parinacota and Iquique provinces), is described and illustrated. Pseudognaphalium munoziae is similar to P. glandulosum but it is principally distinguished by its rosulate basal leaves which are longer than the upper, all of which are apically acute to subobtuse. A key to the species of dwarf Pseudognaphalium occurring in Chile is provided along with a map of their distribution.